Implementation of Task-Based Learning to Improve Learning Outcomes of Islamic Religious Education at State Senior High School - Ubadah, Ubadah; Lucky Ahmad, Andri (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2023)
This study deals with the application of task-based learning methods to improve Islamic Religious Education learning outcomes on Asmaul Husna material in class X State Senior High School 1 Banawa Selatan Donggala Regency with the problem of how to apply task-based learning methods in improving learning outcomes of Islamic Religious Education in participants class X students at State Senior High School 1 Banawa Selatan, Donggala Regency. The study aimed to determine whether the application of task-based learning methods could improve learning outcomes of Islamic Religious Education in class X students at State Senior High School 1 Banawa Selatan, Donggala Regency. The type of research is classroom action research with a qualitative and quantitative approach. The results showed that the learning outcomes obtained by the students of Class X State Senior High School 1 Banawa Selatan improved well, mastery of the Asmaul Husna material, pronunciation, meaning, and meaning and memorized Asmaul Husna. As for the target of the research, which must achieve the Minimum Completeness Criteria of 70, as much as 80% has been successful, even though all students have completed cycle two or the definitive treatment. The study concludes that task-based learning can improve student learning outcomes in Islamic Religious Education subjects, especially the Asmaul Husna material in class X Science, State Senior High School 1 Banawa Selatan.